The Role Of Marketing Entrepreneurial Capability Model In Creating Young Entrepreneurs - Wibowo, Bagus Yunianto; Andi Setiawan; Makmun Riyanto; Noor Suroija; Sandi Supaya (International Journal of Education, Vocational and Social Science, 2024)
Higher education plays a crucial role in fostering young entrepreneurs in Indonesia. The HIEs program has made entrepreneurship its flagship profile to transform the job-seeking culture into a job-creating culture. However, the unemployment rate of graduates continues to rise. Therefore, this study aims to find a solution through the Marketing Entrepreneurial Capability (MECA) model rooted in the Resource-Advantage (R-A) theory. A survey was conducted among 241 entrepreneurial students in Central Java using a questionnaire as a data collection tool. Structural equation modeling techniques were employed to test the reliability and validity of the model. The study's results are expected to contribute to addressing the issue of graduate unemployment by enhancing students' entrepreneurial skills. This research presents a policy model that could serve as a foundation for research and policy-making in higher education in Central Java. The model aims to enhance the connection between the role of higher education and the development of young entrepreneurs (start-ups) by emphasizing Marketing Entrepreneurial Capability (MECA) as a crucial factor. Key Words: Market Orientation, Marketing Entrepreneurial Capability, Product Customization, Service-Offering Customization, Entrepreneurial Performance